Breaking Degeneracies in Formation Histories by Measuring Refractory Content in Gas Giants - Yayaati Chachan; Heather A. Knutson; Joshua Lothringer; Geoffrey A. Blake (The Astrophysical Journal, 2023)
Relating planet formation to atmospheric composition has been a long-standing goal of the planetary science community. So far, most modeling studies have focused on predicting the enrichment of heavy elements and the C/O ratio in giant planet atmospheres. Although this framework provides useful constraints on the potential formation locations of gas giant exoplanets, carbon and oxygen measurements alone are not enough to determine where a given gas giant planet originated. Here, we show that characterizing the abundances of refractory elements (e.g., silicon and iron) can break these degeneracies. Refractory elements are present in the solid phase throughout most of the disk, and their atmospheric abundances therefore reflect the solid-to-gas accretion ratio during formation. We introduce a new framework that parameterizes the atmospheric abundances of gas giant exoplanets in the form of three ratios: Si/H, O/Si, and C/Si. Si/H traces the solid-to-gas accretion ratio of a planet and is loosely equivalent to earlier notions of “metallicity.” For O/Si and C/Si, we present a global picture of their variation with distance and time based on what we know from the solar system meteorites and an updated understanding of the variations of thermal processing within protoplanetary disks. We show that ultrahot Jupiters are ideal targets for atmospheric characterization studies using this framework as we can measure the abundances of refractories, oxygen, and carbon in the gas phase. Finally, we propose that hot Jupiters with silicate clouds and low water abundances might have accreted their envelopes between the soot line and the water snow line.